The demography, spatial ecology and reproductive success of the black rhinoceros, Diceros bicornis, in Hluhluwe-iMfolozi Park, Kwazulu-Natal, South Africa - Nhleko, Zoliswa Nombulelo (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
Black rhinoceroses (Diceros bicornis) are endangered; there are only ~5000 individuals remaining worldwide. Consequently, black rhinos are managed as a metapopulation in southern Africa. This means that even though several sub-populations of black rhinos are geographically separated, they are managed as a single population. This is achieved by interchanging genetic material between the sub-populations. The main aim of the metapopulation management approach is to increase black rhino numbers in the sub-region. The Rhino Management Group (RMG), formed in 1989, was tasked with setting scientifically defensible demographic targets for the remaining black rhino sub-populations in southern Africa. In the same year, the RMG set fecundity rate at 25% and stated that each black rhino sub-population should achieve a minimum growth rate of 5% per year. The black rhino population in the Hluhluwe-iMfolozi Park (HiP), KwaZulu-Natal, South Africa, is of international importance as it has historically been a significant donor population for the translocation of black rhinos to establish new subpopulations elsewhere in the sub-region. However, the black rhino population at HiP is performing poorly in terms of reproductive success. My study was initiated to assess the reproductive life-histories of the black rhino population at HiP and to determine whether the population was meeting the demographic targets set by the RMG. I also wished to assess the use of space by black rhinos in HiP as a potential explanation for the observed reproductive output. Detailed life-history information for known black rhinos (n = 120) was used to investigate reproductive success between 1998 and 2012. The mean age at sexual maturity (ASM) was determined as 12 years, which is higher than the ASM found in black rhino populations that are considered to be performing poorly (ASM = ~ 7 years). The intercalving interval (ICI) was three years, nine months; this was also longer than the ICI of most black rhino populations. Further, the 2012 black rhino population at HiP had a growth rate of 6.4%, and the population comprised 60% adults, 23% sub-adults and 13% juveniles. Such demographics are usually observed in stable populations and it is possible that poor habitat quality could be resulting in the delayed ASM and longer ICI's at HiP. In addition, 5% of the population is removed annually as part of the Black Rhino Range Expansion Program (BRREP) to establish new sub-populations. This could also be negatively influencing the reproductive performance of the HiP population. To determine the home range and habitat use of black rhinos at HiP, field data from 13 individual adult black rhinos (n = 9 females and 4 males) over a two-year period (2011-2012) were analyzed. Black rhino female home ranges were slightly smaller (15.4 ± 12.9 km²) than the home ranges of males (23.3 ±14.0 km²) and both sexes utilized similar habitats in the centre of the park. In addition, both the male and female black rhinos were found closer to rivers and drainage lines than expected. However, the assessment of black rhino space use in HiP was limited by a small sample size, making inferences of the impact of space use on reproductive success difficult. Nevertheless, my study suggests that food availability likely influences the location and sizes of black rhino home ranges at HiP. I believe that my study forms the first step in understanding the factors that influence the reproductive success and habitat use patterns of the current black rhino population at HiP. The information produced by my study should enable park management to identify future research to be conducted at HiP, which will yield more robust data for making informed black rhino management decisions at HiP and elsewhere.
Keywords: Hluhluwe-iMfolozi Park (South Africa); Black rhinoceros -- South Africa -- Hluhluwe; Animal populations -- South Africa -- Hluhluwe; Spatial ecology -- South Africa -- Hluhluwe; Black rhinoceros -- Reproduction